The effects of sex and landing task on hip mechanics - Weinhandl, J. T.; Irmischer, B. S.; Bennett, H. J. (Computer Methods in Biomechanics and Biomedical Engineering, 2021)
Prevalence of femoroacetabular impingement syndrome is common in cutting sports. A first step to understanding the relationship between cutting sports and the development of femoroacetabular impingement is to investigate hip joint contact forces during such tasks. The purpose of this study was to explore sex and task differences in hip joint contact forces, estimated through musculoskeletal modeling, during single-leg drop landings and land-and-cuts. Kinematics and ground reaction forces were obtained from 38 adults performing drop landings and land-and-cut tasks. Simulations were performed in OpenSim to estimate lower extremity muscle forces and hip joint contact forces. Statistical parametric mapping was used to compare hip joint force waveforms between sex and task. There were no sex differences in hip joint forces, but landing trials were characterized by increased hip joint forces compared to land-and-cut trials. The hip joint force estimates obtained the current study could be used in future finite element models that incorporate bone growth models to understand the development of femoroacetabular impingement and design possible compensatory exercises.